Optimizing Recovery: Early Versus Delayed Chest Tube Removal in Pediatric Cardiac Surgery Patients: A Randomized Controlled Trial - Abdulraouf M.Z. Jijeh, MD; Ghassan A. Shaath, MD; Sameh R. Ismail, MD; Mohamed S. Kabbani, PhD; Omar M. Hijazi, MD; Hayan Altaweel, MD; Husam Hamada, MD; Ammar Qadi, MD; Anis Fatima, MD; Abdrabo Abdrabo, MD; Wiaam Ahmed, MD; Nuha Ahmed, MD; et al. (Critical Care Explorations)
OBJECTIVES:. To evaluate the safety and efficacy of an early chest tube removal protocol in reducing tube duration without increasing complications following pediatric cardiac surgery. DESIGN:. A single-center, randomized controlled trial. SETTING:. Pediatric cardiac ICU. PATIENTS:. Two hundred fifteen pediatric patients with chest tubes after cardiac surgery. INTERVENTIONS:. Patients were randomized to early removal (drainage threshold < 6 mL/kg over 8 hr) or late removal (24-hr assessment) groups. Primary outcomes included chest tube duration, whereas secondary outcomes encompassed ICU stay, ventilation time, hospital stay, and complication rates. MEASUREMENTS AND MAIN RESULTS:. Median chest tube duration was significantly shorter in the early removal group (3 d) compared with the late removal group (4.9 d; p < 0.0001). Rates of fluid reaccumulation and pneumothorax were low and comparable between groups. Notably, no patients in either group required tube reinsertion. ICU and total hospital stay durations were similar across groups. CONCLUSIONS:. An early chest tube removal protocol following pediatric cardiac surgery suggests a reduction in chest tube duration without increasing the risk of complications. These findings support the adoption of an evidence-based early removal approach to enhance patient comfort and optimize ICU resource utilization in pediatric cardiac surgery patients.